2017
DOI: 10.1093/jcr/ucx046
|View full text |Cite
|
Sign up to set email alerts
|

Round Off the Bargaining: The Effects of Offer Roundness on Willingness to Accept

Abstract: This research shows that making a precise (vs. round) offer in a negotiation may lead to diverging outcomes. On the one hand, past literature has demonstrated a precision advantage wherein offer precision reduces the amount by which offer recipients counter. On the other hand, building on the notion that round numbers symbolize completion and previous findings that individuals tend to set goals at round numbers, we hypothesize a roundness advantage wherein offer roundness increases the bargainer's willingness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Such costs may impact audiences' interactions differently. Some studies found users have round-number goal, and they prefer to purchase near a half-hour interval online (e.g., 19:28, 00:24) [32,33]. Likewise, live streaming which start near round-number time may get more comments (H4).…”
Section: Plos Onementioning
confidence: 99%
“…Such costs may impact audiences' interactions differently. Some studies found users have round-number goal, and they prefer to purchase near a half-hour interval online (e.g., 19:28, 00:24) [32,33]. Likewise, live streaming which start near round-number time may get more comments (H4).…”
Section: Plos Onementioning
confidence: 99%
“…For example, attributes described by rounded numbers (e.g., 20, 30) are perceived to be more stable than those described by nonrounded ones (27, 32). Consequently, product attributes are inferred to be more enduring if they are described in round numbers (100 mg) than if they are described in precise numbers (102 mg) (Pena‐Marin & Bhargave, ) and offers in round numbers are inferred to be more resistant to change in a bargaining context and therefore are more likely to be accepted (Yan & Pena‐Marin, ).…”
Section: Applicationsmentioning
confidence: 99%
“…Similar attributions are made based on whether the number is in digital or written form or expressed as round numbers. Numbers in digital form are perceived to be more technological (Pavia & Costa, 1993), and round numbers are associated with greater product completeness (Gunasti & Ozcan, 2016;Yan & Pena-Marin, 2017) and femininity (Yan, 2016).…”
Section: Language Complexitymentioning
confidence: 99%
“…Granularity effects have also been observed in the use of integers (3) versus finer-grain decimals (2.4). Not only does the granularity of the number Klink (2000), Lowrey and Shrum (2007), Maglio et al (2014), Topolinski et al (2015), Yorkston and Menon (2004) Positive effects on preferences maximized when symbolism is congruent with expectations Numbers Associated with perceptions of technology Gunasti and Ozcan (2016), Pavia and Costa (1993), Yan and Pena-Marin (2017), Zhang and Schwarz (2012) Granularity influences inferences and expectations Roundedness associated with perceptions of completeness Sound repetition: alliteration and rhyme Alliteration and rhyme aid memory Argo et al (2010), Davis et al (2016), Filkukov a and Klempe (2013), McGlone and Tofighbakhsh (2000) Rhymes increase processing fluency Influence liking, perceptions of truthfulness Pronunciation (Ease)…”
Section: Language Complexitymentioning
confidence: 99%
See 1 more Smart Citation